Innovative assessment based on multimedia proofs and social network sharing for introductory engineering courses - Correcher, Antonio; Ricolfe-Viala, Carlos; Ivorra, Eugenio; Cordero, Fernando; Blanes, Carlos; Martínez-Turégano, Jaime (Frontiers in Education, 2025)
Training and education quality are crucial worldwide even more in the area of technical vocation. The assessment validates the performance of the training and education process, however, the design of assessments that validate the acquisition of certain knowledge, abilities or competences is still unsolved and remains open for research. In this paper, the advance in new technologies is used in the assessment process in a step ahead. Since social media is a big part of the daily life for lots of students, an assessment method is proposed that uses social media as the learning motivation. In consequence, the proposed assessment method is completely aligned with the student way of life and this fact motivates the student learning process since generating new high impact social media contents is a very challenging task. The paper shows the results of an assessment innovation project in which the authors develop a methodology for evaluating laboratory practices that measures knowledge of introductory concepts in automatic control engineering courses. The innovation aims to actively involve students in the generation of social media resources through modern technologies that are attractive to them. Under this methodology, students are tasked with creating a series of short videos explaining how to solve a specific problem or elucidate a concept covered in theory lessons. These videos are shared with their peers via a social network. Lecturers evaluate videos considering the quality in the explanation of technical concepts and impact in the social network. Results show that the proposed assessment methodology increases student motivation compared to the traditional assessment process and increases marks.